ANALYSIS OF ROAD CAPACITY AND TRAFFIC PERFORMANCE ON JENDRAL SOEHARTO STREET KUPANG - Amy Wadu (Universitas Islam Malang, 2020)
Jendral Soeharto street is one of the streets in Kupang. On this street, traffic jams often occur during peak hours. This study aims to determine the capacity and performance of existing traffic on Jalan Jendral Suharto. This study was analyzed using the Indonesian Road Capacity Guidelines (PKJI2014). Traffic performance analysis begins by calculating traffic flow at peak hours, road side friction, road capacity, degree of saturation, and analysis of space mean speed. The results of the traffic performance analysis show that the degree of saturation (DS) or v/c ratio in the existing conditions has a value of > 0.75, which is 0.98.